Dynamic Programming - Borne, Pierre; Filip, Florin Gheorghe; Stefanoiu, Dan; Popescu, Dumitru (Optimization in Engineering Sciences, 2012)
This chapter introduces the concept of dynamic programming with various application examples, from an engineering point of view. The chapter first presents principle of dynamic programming and recurrence equation of optimality. Next, the chapter discusses particular cases of optimization problems, including the infinite horizon stationary problem, variable horizon problem, random horizon problem, sum‐like constraints, and the random evolution law.